Ensuring halal compliance in agrifood systems: A review of concepts, principles, and advanced technologies - Saputra, Ramadhan; Jannah, Ghaitsaa Puteri Rhaudatul; Sipahutar, Aviliani; Hidayati, Nurul; Casim, Rahsdi M. (Halal Studies and Society, 2025)
The global halal market is witnessing rapid expansion driven by increased demand from Muslim consumers. This necessitates strict adherence to Islamic dietary rules throughout the agri-food supply chain. However, inconsistencies in halal certification standards, complexity of supply chains, and lack of global standardization raised concerns about the integrity and authenticity of halal products. Therefore, this research aims to explore the core concepts and ethical foundations of halal in food industry, emphasizing the balance between sustainability and humane practices. The critical role of advanced technologies is also reported, such as DNA testing, blockchain, sensors, and artificial intelligence, in ensuring traceability, transparency, and contamination prevention within halal food chains. The results show that the implementation of quality management systems is discussed as a fundamental method for maintaining halal compliance, with clear policies, procedures, and performance evaluations essential for effective assurance. This research suggests the necessity of technological integration and quality management to strengthen consumer trust and global competitiveness in halal food industry.